Long Non-coding RNA GAS5 Regulates T Cell Functions via miR21-Mediated Signaling in People Living With HIV - Nguyen, Lam Ngoc Thao; Nguyen, Lam Nhat; Zhao, Juan; Schank, Madison; Dang, Xindi; Cao, Dechao; Khanal, Sushant; Chand Thakuri, Bal Krishna; Lu, Zeyuan; Zhang, Jinyu; Li, Zhengke; Morrison, Zheng D.; et al. (Frontiers in Immunology, 2021)
T cells are critical for the control of viral infections and T cell responses are regulated by a dynamic network of non-coding RNAs, including microRNAs (miR) and long non-coding RNAs (lncRNA). Here we show that an activation-induced decline of lncRNA growth arrest-specific transcript 5 (GAS5) activates DNA damage response (DDR), and regulates cellular functions and apoptosis in CD4 T cells derived from people living with HIV (PLHIV) via upregulation of miR-21. Notably, GAS5-miR21-mediated DDR and T cell dysfunction are observed in PLHIV on antiretroviral therapy (ART), who often exhibit immune activation due to low-grade inflammation despite robust virologic control. We found that GAS5 negatively regulates miR-21 expression, which in turn controls critical signaling pathways involved in DNA damage and cellular response. The sustained stimulation of T cells decreased GAS5, increased miR-21 and, as a result, caused dysfunction and apoptosis in CD4 T cells. Importantly, this inflammation-driven T cell over-activation and aberrant apoptosis in ART-controlled PLHIV and healthy subjects (HS) could be reversed by antagonizing the GAS5-miR-21 axis. Also, mutation of the miR-21 binding site on exon 4 of GAS5 gene to generate a GAS5 mutant abolished its ability to regulate miR-21 expression as well as T cell activation and apoptosis markers compared to the wild-type GAS5 transcript. Our data suggest that GAS5 regulates TCR-mediated activation and apoptosis in CD4 T cells during HIV infection through miR-21-mediated signaling. However, GAS5 effects on T cell exhaustion during HIV infection may be mediated by a mechanism beyond the GAS5-miR-21-mediated signaling. These results indicate that targeting the GAS5-miR-21 axis may improve activity and longevity of CD4 T cells in ART-treated PLHIV. This approach may also be useful for targeting other infectious or inflammatory diseases associated with T cell over-activation, exhaustion, and premature immune aging.